Effect of Ultrafine Grinding on the Structural and Functional Properties of Flaxseed Protein - Yali LIANG; Ronghua GAO; Narisu QIN; Xiaolan BAO (Shipin gongye ke-ji)
To enhance the functional properties of flaxseed protein and broaden its application in food production, ultrafine-ground flaxseed was obtained using a high-energy nano-impact mill. The structure and functional characteristics of flaxseed protein were analyzed by scanning electron microscopy, sodium dodecyl sulfate polyacrylamide gel electrophoresis, Fourier transform infrared spectroscopy, and endogenous fluorescence spectroscopy. Results showed that, ultrafine grinding converted the large smooth-surfaced flakes of flaxseed into irregular particles. With the extension of ultrafine grinding time, a significant reduction in the average particle size of flaxseed protein (P<0.05) and in the surface sulfhydryl (S-SH) content was observed, whereas significant increased were detected in surface hydrophobicity (H0), fluorescence intensity, and zeta potential (P<0.05). Although the molecular weight of flaxseed protein was not significantly affected by ultrafine grinding treatment, an increase in α-helix content was observed, while the contents of β-sheets, β-turns, and random coils were reduced, indicating a change in protein secondary structure. Functional property analyses revealed significant improvements in the solubility, water-holding capacity, emulsifying activity index (EAI), emulsion stability index (ESI), foaming capacity (FC), and foam stability (FS) of flaxseed protein following ultrafine grinding (P<0.05). Pearson correlation analysis indicated that particle size, S-SH, and β-sheets were significant negatively correlated with solubility (P<0.05), whereas H0 and α-helices were positively correlated with solubility, EAI, and ESI. Solubility was positively correlated with ESI, EAI, FS, and FC (P<0.05). In summary, ultrafine grinding treatment was demonstrated to enhance the solubility of flaxseed protein by altering its secondary and tertiary structures, thereby improving functional properties such as EAI, ESI, FS, and FC. This finding indicated that moderate ultrafine grinding can enhance the functional properties of flaxseed protein and thus represents an effective flaxseed protein modification technology.